Implementation of Five Calls Reminder (FCR) as the Adaptive Muroja’ah (Memorization) Method for the Qur’an at Daarunnajah Magelang Islamic Boarding School - Sangadah, Laila; Ismail, Safiyah (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2020)
Today there are many educational institutions, both formal and non-formal, that make tahfidzul Qur'an one of their particular programs. It is not uncommon for formal schools to incorporate tahfidz material into their curriculum structure. This study aims to determine the effectiveness of the Five Calls Reminder (FCR) application as a method of reciting adaptive memorization (muroja’ah) for the Qur'an in Daarunnajah Magelang Islamic Boarding School. This research uses qualitative methods using descriptive analysis. Data collection was performed through observation, interviews, and documentation. The results of this study indicate that the Five Calls Reminder (FCR) method was created to make it easier for Qur’an memorizers with double busyness in safeguarding their memorization continuously. The FCR method is applied by students who memorize Qur’an at the Daarunnajah Magelang Islamic Boarding School as an independent effort for students to memorize the Qur’an. This method positively affects the implementation of the Qur'anic tahfidz at the Daarunnajah Magelang Islamic Boarding School. With the FCR method, student memorizers enjoy the muroja’ah process more comfortably without clashing with the madrasah's schedule or assignments. This research provides an alternative view of the tahfidz method, which is useful in implementing the tahfidzul Qur'an program.